Microfluidic droplet encapsulation of highly motile single zoospores for phenotypic screening of an antioomycete chemical - Yang, Haifeng (American Institute of Physics, 2011)
Highly motile Phytophthora sojae (P. sojae) zoospores of an oomycete plant pathogen and antioomycete candidate chemicals were encapsulated into microdroplets. Random fast self-motion of P. sojae zoospores was overcome by choosing an appropriate flow rate for a zoospore suspension. To influence stochastic loading of zoospores into a microfluidic channel, a zoospore suspension was directly preloaded into a microtubing with a largely reduced inner diameter. A relatively high single zoospore encapsulation rate of 60.5% was achieved on a most trivial T-junction droplet generator platform, without involving any specially designed channel geometry. We speculated that spatial reduction in the diameter direction of microtubing added a degree of zoospore ordering in the longitudinal direction of microtubing and thus influenced positively to change the inherent limitation of stochastic encapsulation of zoospores. Comparative phenotypic study of a plant oomycete pathogen at a single zoospore level had not been achieved earlier. Phenotypic changes of zoospores responding to various chemical concentration conditions were measured in multiple droplets in parallel, providing a reliable data set and thus an improved statistic at a low chemical consumption. Since each droplet compartment contained a single zoospore, we were able to track the germinating history of individual zoospores without being interfered by other germinating zoospores, achieving a high spatial resolution. By adapting some existing droplet immobilization and concentration gradient generation techniques, the droplet approach could potentially lead to a medium-to-high throughput, reliable screening assay for chemicals against many other highly motile zoospores of pathogens.